Motivational Messages in “Hamzah” Poems by Fadwa Tuqan: Gorys Keraf's Semantic Study - Chamidah, Richayatul; Wahyudi, Jarot (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
This research discusses the study of meaning in linguistics including connotation and denotation meaning. The purpose of this research is to reveal the connotative meaning in the poem "Hamzah". The poem "Hamzah" tells about the memory of the Palestinian people's past of the Israeli occupation. This research is an interpretative descriptive research to examine the meaning in depth. Primary data is obtained from poems that contain connotative meanings. Gorys Keraf's semantics is the theory used by the author to dissect the layered meanings. The results in this study reveal that the connotation meaning expressed by the author is a motivation. The meaning has complex layers includes pain, bad memories and the spirit of Fadwa's struggle as a Palestinian. There are eight stanzas that contain connotational meaning. The stanzas contain: pain in stanza eighth, worry in stanza eleventh, lamentation in stanzas twelfth and forty fourth, praise in stanza thirteenth, and encouragement in stanza thirty seventh. Meanwhile, the connotation meaning in the poem is attached to the whole stanza of the poem in addition to the connotation words. The words are intended as motivation and a form of resistance from the Israeli occupation.